Photoelectrochemical-Type Photodetectors Based on Ball Milling InSe for Underwater Optoelectronic Devices - Yi Xu; Junxin Zhou; Dongyue Tian; Zhendong Fu; Yuewu Huang; Wei Feng (Nanomaterials)
In this paper, InSe nanosheets were synthesized by a ball milling method, and photoelectrochemical-type photodetectors (PEC PDs) based on the ball milling InSe (M-InSe) were fabricated using simulated seawater as the electrolyte. M-InSe nanosheets show good absorption in the visible region of 450–600 nm. The M-InSe PEC PDs display a good self-powered photoresponse under 525 nm irradiation, including a high responsivity of 0.8 mA/W, fast response time of 28/300 ms, and good stability. Furthermore, the InSe PEC PDs successfully demonstrated prototype application in wireless underwater optical communication and optical imaging. These results demonstrate that M-InSe holds good application prospects in underwater optoelectronic devices.